Growth of Chrysanthemum grandiflorum in different peats and change of peat properties during cultivation - Beckmann-Cavalcante, M. Z. [UNESP]; Lopes-Pivetta, K. F. [UNESP]; Meinken, E.; Roeber, R. (My University, 2009)
Marketable chrysanthemums were produced in several different peat types. Only the plants in one of the dredged frozen black peats and one of the milled white peats had a significant lower shoot dry weight than those in one of the sod and milled white peats, respectively. As the N-contents of the fertilized peats show neither deficiency nor excess in nutrient supply, possibly they are not the reason for the differences in shoot dry weight. The air capacity, which is extremely low in both dredged frozen black peats and dropped further during the cultivation period due to decomposition, also cannot explain the differences in shoot dry weight sufficiently (R2=0.44*; n=12). A close linear negative correlation (R2=0.77** n=12) was found between the CAT (VDLUFA) soluble Fe and the shoot dry weight. Therefore, the Fecontents might be a quality factor of peat to be used as a growing medium.
Keywords: Chrysanthemum; Growing media; Horticultural substrates; Peat properties; Grandiflorum